2017
DOI: 10.1111/nin.12191
|View full text |Cite
|
Sign up to set email alerts
|

A role for virtue in unifying the ‘knowledge’ and ‘caring’ discourses in nursing theory

Abstract: A critical examination of contemporary nursing theory suggests that two distinct discourses coexist within this field. On the one hand, proponents of the 'knowledge discourse' argue that nurses should drop the 'virtue script' and focus on the scientific and technical aspects of their work. On the other hand, proponents of the 'caring discourse' promote a view of nursing that embodies humanistic qualities such as compassion, empathy and mutuality. In view of this, we suggest a way to reconcile both discourses d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…This relationship indicates that the growth of professional identity may be related to increasing the interest to the profession or vice versa. While the literature related to the correlation between job satisfaction and moral competencies is limited, the results from a research showed that there could be a relationship between these two variables [28]. We did not find any studies that assess the relationship between moral development and professional identity formation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This relationship indicates that the growth of professional identity may be related to increasing the interest to the profession or vice versa. While the literature related to the correlation between job satisfaction and moral competencies is limited, the results from a research showed that there could be a relationship between these two variables [28]. We did not find any studies that assess the relationship between moral development and professional identity formation.…”
Section: Discussionmentioning
confidence: 66%
“…They concluded that in order to have higher moral practice in nursing students, nursing instructors should promote the students' professional identity. Bliss, Baltzly [28] argued that the nurse's professional identity associates their practice with the relationship between them and patients, which morality is one of its most important dimensions [29]. Some scholars argued that professional values, including moral values, are essential in the formation of professional identity in nursing students [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…It does not begin and end when one arrives to and leaves work. Several nursing scholars advocate for virtue ethics in nursing including Armstrong (2006) , Arries (2005) , Bliss, Baltzy, Bull, Dalton, and Jones (2017) , Brody (1988) , and Lutzen and Barbosa da Silva (1996) .…”
Section: Normative Ethicsmentioning
confidence: 99%
“…The concluded that in order to higher moral practice in nursing students, nursing instructors should promote the professional identity them. Bliss, Baltzly (29) argued that the nurse's professional identity associates their practice with the care relationship between them and patients, which morality is one of its most important dimensions (30). Some scholars argued that professional values, including moral values, are essential in the formation of professional identity in nursing students (31,32).…”
Section: Introductionmentioning
confidence: 99%